Analyzing the Use of Recycled Materials in Sustainable Concrete in the GCC Countries - Alsalama, Salem Mohamad; Damdelen, Omer (Technium Sustainability, 2022)
The modern construction industry is based on the development of concrete structures and concrete is the most commonly used building material for the construction industry. Concrete manufacturing involves dev elopement of a mixture containing different natural resources like stone, clay, sand, water, and cement. These natural resources are extracted and transported to the construction site to create concrete (Ahmad et al., 2022). On the other side, concrete waste poses a significant environmental and economic challenge for the global construction industry. The present study is based on analyzing the use of recycled material for the development of sustainable concrete mix. Recycled materials involve the recycling of construction waste that provides the best alternative for natural resources and helps to prevent the environment. The present study is based on qualitative data analysis and surveys to highlight the usage of recycled materials to develop sustainable concrete. The survey results demonstrate that recycled materials are significantly important for the development of concrete mix and it is cost-effective and also protect the environment. The present research provides a deep insight into the usage of recycled materials for sustainable concrete manufacturing.